Countering beta-cypermethrin: partitioning roles of the insect gut and its bacteria - Bai, Li; Cai, Xiao-Lin; Li, Man-Yu; Wang, Fu-Xiao; Zou, Chuan-Shan; Zhang, Jun-Sheng; Xie, Ming-Yu; Qi, Feng-Hui; Jing, Tian-Zhong (Journal of Pest Science, 2023)
Insects and their gut bacteria can degrade insecticides separately, which is helpful for insecticide resistance development. However, there is little knowledge about insect and gut bacteria cooperation or their respective roles in an insecticide degradation complex. In this study, we investigated the activities of three enzymes related to pesticide degradation in a leaf beetle, Ambrostoma quadriimpressum Motschulsky. The activities of glutathione S-transferase (GST), carboxylesterase (CarE), and catalase (CAT) were up-regulated in the holo-gut (including lumen) after 5 days of exposure to beta-cypermethrin. The roles of the beetle gut and its bacteria were partitioned via transcriptome sequencing and 16S rDNA sequencing. The results showed that the elevated activities of CarE were attributed to the beetle gut, whereas GST and CAT were attributed to its bacteria. Pathway enrichment analysis based on a reference database hybridized with the BioCyc and KEGG databases showed that the gluconeogenesis pathway plays an important role in the gut of the beetle to counter the insecticide. The guts may be injured by the insecticide, and the epithelial cells regenerated via the Hippo signaling pathway activated by glutamate. The results from PICRUSt 2 and LEfSe showed a possible community pathway degrading the insecticide in the gut, i.e., beta-cypermethrin was degraded into intermediates (e.g., protocatechuate and catechol) and subsequently degraded by gut bacteria via the ortho- or meta-cleavage pathway.